Self-care behaviour and associated factors among heart failure patients in Ethiopia: a systematic review and meta-analysis - Addisu Getie; Adam Wondmieneh; Melaku Bimerew (BMJ Open)
Objective This study aimed to estimate the pooled level of self-care behaviour among heart failure patients in Ethiopia.Design Systematic review and meta-analysis.Data source PubMed/MEDLINE, HINARI, Web of Sciences, Scopus, Google Scholar, Science Direct, African journals online and University repositories were searched from 1 January 2000 to 1 November 2023.Eligibility criteria We include studies that examined self-care behaviour among heart failure patients, studies that report factors associated with self-care behaviour and observational studies (cross-sectional, case-control and cohort) with full text available.Data extraction and synthesis The data were extracted with Microsoft Excel and analysed by using STATA V.11 software. The weighted inverse variance random-effects model at 95% CI was used to estimate the pooled level of self-care behaviour and its associated factors among heart failure patients. Tests of heterogeneity, test of publication bias and subgroup analyses were also employed.Results Thirteen cross-sectional studies with 4321 study participants were included; and the pooled level of good self-care behaviour among heart failure patients in Ethiopia was found to be 38.3% (95% CI 31.46 to 45.13). Only 68.8% of heart failure patients were knowledgeable about heart failure. Knowledge about heart failure (Adjusted Odds Ratio (AOR)=3.39; 95% CI 2.42 to 4.74) and absence of comorbidity (AOR=2.69; 95% CI 1.35 to 5.37) were significantly associated with good self-care behaviour among heart failure patients in Ethiopia.Conclusion The majority of heart failure patients in Ethiopia did not adhere to the recommended self-care behaviours. Nearly one-third of heart failure patients were not knowledgeable about heart failure. Knowledge about heart failure and the absence of comorbidities were significantly associated with good self-care behaviour. Therefore, efforts should be devoted to increasing knowledge and preventing comorbidities among heart failure patients.PROSPERO registration number CRD42023394373.